KERJASAMA GURU PAK DAN ORANG TUA DALAM MEMBENTUK TINGKAH LAKU SISWA - Lamria Gultom (Pusat Riset dan Inovasi Nasional, 2023)
ABSTRACT, The cooperation that is built between Christian Religious Education Teachers and parents has a very important role to foster student behavior in the form of: streamlining meetings between Christian Religious Education teachers and parents, Christian Religious Education teachers making visits to students' homes, up to giving material donations and spiritual which aims at forming student behavior that is in accordance with Christian values. Christian Religious Education teachers and parents must have the ability to direct students to have good behavior, such as: firm faith in God, discipline, upholding ethical values, good personality, skilled, independent and responsible. By having such behavior, students indirectly become bearers of joy or peace in the family, at school and in society.